Exploring challenges to sustainable practices in India's metal sector using DEMATEL approach - Pradeep Kumar; Vinod Yadav; Milind Kumar Sharma (Discover Sustainability)
Abstract The metal industry significantly contributes to India's manufacturing sector and plays a vital role in the country's GDP growth. However the manufacturing of metal has many impacts on the environment, so the adoption of sustainable practices for the metal industry is very important, but it faces significant challenges for adopting the sustainable practices. Firstly, 14 challenges are identified from the literature review and discussion with experts. Later, the Decision-Making Trial and Evaluation Laboratory approach was applied to these challenges to prioritize the identified challenges and the cause-effect relationships among them, and the obtained ranking was validated by doing the sensitivity analysis of the model. From these findings, we identified that lack of infrastructure (C9), high energy consumption (C3), advanced technology adoption for sustainability (C5), demand/market of circular products (C6), and material sorting and segregation in reverse logistics (C14) are the key challenges. These key challenges can be mitigated by key practitioners and managers through the insights provided in this paper.